Human preprocalcitonin self-antigen generates TAP-dependent and -independent epitopes triggering optimised T-cell responses toward immune-escaped tumours. Issue 1 (December 2018) - Durgeau, Aurélie; Virk, Yasemin; Gros, Gwendoline; Voilin, Elodie; Corgnac, Stéphanie; Djenidi, Fayçal; Salmon, Jérôme; Adam, Julien; Montpréville, Vincent; Validire, Pierre; Ferrone, Soldano; Chouaib, Salem; et al.
Abstract Tumours often evade CD8 T-cell immunity by downregulating TAP. T-cell epitopes associated with impaired peptide processing are immunogenic non-mutated neoantigens that emerge during tumour immune evasion. The preprocalcitonin (ppCT)16–25 neoepitope belongs to this category of antigens. Here we show that most human lung tumours display altered expression of TAP and frequently express ppCT self-antigen. We also show that ppCT includes HLA-A2-restricted epitopes that are processed by TAP-independent and -dependent pathways. Processing occurs in either the endoplasmic reticulum, by signal peptidase and signal peptide peptidase, or in the cytosol after release of a signal peptide precursor or retrotranslocation of a procalcitonin substrate by endoplasmic-reticulum-associated degradation. Remarkably, ppCT peptide-based immunotherapy induces efficient T-cell responses toward antigen processing and presenting machinery-impaired tumours transplanted into HLA-A*0201-transgenic mice and in NOD-scid-Il2rγ null mice adoptively transferred with human PBMC. Thus, ppCT-specific T lymphocytes are promising effectors for treatment of tumours that have escaped immune recognition. Tumours can escape CD8 T-cell immunity by down-regulating antigen presentation machinery components, such as TAP. Here the authors describe tumour antigenic peptides processed by TAP-independent and -dependent pathways and show in mouse models that these peptides can be exploited to induce antitumor T-cell activity when TAP expression is downregulated.